Effect of toothpaste with high fluoride concentration on remineralization of dental substrate with artificial caries - Diego Felipe Mardegan GONÇALVES; Érika Mayumi OMOTO; Yasmine Parischi MUSA ALI; André Luiz Fraga BRISO; Ticiane Cestari FAGUNDES (Revista de Odontologia da UNESP, 2023)
Abstract Introduction fluoride toothpaste is widely used by the population. Objective dentifrices with a high concentration of sodium fluoride and the presence of tricalcium phosphate were developed, providing additional protection to patients vulnerable to the development of caries. This study aimed to evaluate the influence of different dentifrices on the surface and internal hardness and enamel wear after artificial caries, pH cycling, and toothbrushing. Material and method enamel blocks (4x4 mm) were obtained from 20 bovine teeth. The specimens were submitted to artificial caries lesion and then to pH cycling and brushing according to the dentifrice: Colgate Total 12 and Clinpro + Tricalcium Phosphate. Result after this period, they were submitted to analysis of superficial and internal hardness and profilometry. Scanning Electron Microscopy (SEM) was performed. The data obtained were evaluated by one-way Analysis of Variance (ANOVA) to evaluate the mineral recovery and profilometry, and two-way repeated measures ANOVA to evaluate the superficial and internal hardness. Conclusion analyzing the surface hardness, after caries induction, there was a significant reduction in hardness that was partially recovered regardless of the dentifrice used. For internal hardness, Clinpro obtained lower values on the control side and up to 90 micrometers on the test side. As for profilometry, Colgate Total 12 showed greater wear when compared to Clinpro. It was concluded that Clinpro promoted lower internal hardness, however, Colgate Total 12 resulted in greater surface wear of tooth enamel.